Bioremediation - Baker, Katherine H. (McGraw-Hill, 1994)
The book presents the basic techniques of bioremediation and applications dealing with with the major classes of chemical pollutants, such as hydrocarbons, solvents, PCBs and dioxins, and pesticides. It also offers information on the design and use of bioreactors to treat contaminated soil and grounwater; the design and interpretation of bioremediation feasibility studies; the legal and regulatory aspects of bioremediation